An investigative study to style reading: The style of Cristobal Balenciaga interpreted by contemporary fashion designers - RANATHUNGA G. M.; WIJESUNDARA K.M.S.V (Journal of Advanced Research in Social Sciences and Humanities, 2021)
Aim: There is a constant recycling of old looks into the current fashion scene. Many working fashion designers today mine haute couture and the works of other high-end designers for inspiration. Fashion designer Cristobal Balenciaga (1895-1972), often called the